Recognition features of felsic pyroclastics of Serra do Tombo formation, Minas Gerais, Brazil. (March 2016) - de Castro Paes, Vinícius José; Ozanam Raposo, Frederico; Chaves Sgarbi, Geraldo Norberto; Schiazza, Mariangela; Stoppa, Francesco
Abstract: In this contribution we report a study of poorly exposed, rhyodacitic welded-ignimbrite deposit from Minas Gerais. A petrographic study of textures indicate high temperature of emplacement. Key features include eutaxitic texture, flattened and agglutinated lapilli and glass menisci. Most of the feldspar minerals and glass are extensively altered to clay minerals, which pseudomorph the original volcanic textures. Glass menisci and spherules suggest a possible process of liquid immiscibility. Immobile trace element distribution indicates a possible link with other post-Palaeozoic felsic volcanic rocks in Brazil, a magmatism interpreted as due to basaltic underplating and partial melting of a hydrous continental crust. A peculiar feature is a high Light REE/Heavy REE ratio. Depletion in heavy rare earth elements is possibly due to a residual HREE-bearing phase in the source. The geologic context of these rocks suggests a Lower Cretaceous age and a tectonic relationship with a continental rifting event. Graphical abstract: Highlights: Lower Cretaceous, rhyodacitic Serra do Tombo ignimbrite occurs in Minas Gerais. Flow-banded, eutaxitic texture and flattened and agglutinate lapilli occur. Two kind of glasses and glass menisci indicate liquid immiscibility. Geochemistry suggests continental crust melting by underplating.